Effects of latent toxoplasmosis on autoimmune thyroid diseases in pregnancy - Kaňková, Šárka; Procházková, Lucie; Flegr, Jaroslav; Calda, Pavel; Springer, Drahomíra; Potluková, Eliška (PLoS One, 2014)
BACKGROUND: Toxoplasmosis, one of the most common zoonotic diseases worldwide, can induce various hormonal and behavioural alterations in infected hosts, and its most common form, latent toxoplasmosis, influences the course of pregnancy. Autoimmune thyroid diseases (AITD) belong to the well-defined risk factors for adverse pregnancy outcomes. The aim of this study was to investigate whether there is a link between latent toxoplasmosis and maternal AITD in pregnancy. METHODS: Cross-sectional study in 1248 consecutive pregnant women in the 9-12th gestational weeks. Serum thyroid-stimulating hormone (TSH), thyroperoxidase antibodies (TPOAb), and free thyroxine (FT4) were assessed by chemiluminescence; the Toxoplasma status was detected by the complement fixation test (CFT) and anti-Toxoplasma IgG enzyme-linked immunosorbent assay (ELISA). RESULTS: Overall, 22.5% of the women were positive for latent toxoplasmosis and 14.7% were screened positive for AITD. Women with latent toxoplasmosis had more often highly elevated TPOAb than the Toxoplasma-negative ones (p = 0.004), and latent toxoplasmosis was associated with decrease in serum TSH levels (p = 0.049). Moreover, we found a positive correlation between FT4 and the index of positivity for anti-Toxoplasma IgG antibodies (p = 0.033), which was even stronger in the TPOAb-positive Toxoplasma-positive women, (p = 0.014), as well as a positive correlation between FT4 and log2 CFT (p = 0.009). CONCLUSIONS: Latent toxoplasmosis was associated with a mild increase in thyroid hormone production in pregnancy. The observed Toxoplasma-associated changes in the parameters of AITD are mild and do not seem to be clinically relevant; however, they could provide new clues to the complex pathogenesis of autoimmune thyroid diseases.
Keywords: Thyroid Diseases; hormony štítné žlázy; Czech Republic; toxoplazmóza; Female; Humans; lidé; autoprotilátky; Immunoglobulin G; Toxoplasmosis; Cross-Sectional Studies; Middle Aged; protilátky protozoální; ženské pohlaví; lidé středního věku; nemoci štítné žlázy; Pregnancy Outcome; těhotenství; výsledek těhotenství; Česká republika; mladiství; rizikové faktory; autoimunitní nemoci; komplikace těhotenství; Young Adult; Adolescent; Pregnancy Complications; Autoimmune Diseases; mladý dospělý; Thyroid Hormones; imunoglobulin G; Autoantibodies; Risk Factors; dospělí; Pregnancy; Adult; Antibodies, Protozoan; průřezové studie